AKBARNAMA-- DELINEATING TERRITORIAL EXPANSION UNDER AKBAR - Birendra Kumar1 (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The notion of territoriality is coterminous with the construction of history of imperial expansion under the reign of the Mughal Badshah Akbar. It becomes more impressive when it is constructed on the basis of primary sources like Akbarnama of Abul Fazl. In this article, I have endeavoured to construct the history of territorial expansion under Akbar particularly in the very context of ‘endogamous processes’ followed by vertical, horizontal and assimilative processes of state formation, acculturation of tribal populations and integration of local foci and religious cults s well as practices resulting in the consolidation of the Mughal empire under the reign of Akbar. Here, an effort has been made to construe the frontier policy of Akbar and how the geo-strategic location were extremely important for him at that time and space or for any other rulers of the present times.